Therapeutic potential of botanical drugs and their metabolites in the treatment of pelvic inflammatory disease - Zhong, Han-Zhi; Yan, Pei-Jia; Gao, Qi-Feng; Wu, Jue; Ji, Xiao-Li; Wei, Shao-Bin (Frontiers in Pharmacology, 2025)
The application of botanical drugs and their metabolites in the treatment of pelvic inflammatory disease (PID) has garnered significant attention. Owing to their broad-spectrum activity, global accessibility, and structural diversity, botanical drugs have emerged as promising candidates for adjunctive or alternative therapies. This review systematically summarizes botanical drugs and their metabolites, focusing on their antimicrobial potential against endogenous and exogenous pathogens associated with PID. Specifically, it addresses various underlying antibacterial mechanisms, including interference with bacterial cell membranes and cell walls, inhibition of pathogen-specific efflux pumps, modulation of pathogen-related gene expression, and synergistic effects when combined with conventional antibiotics. This review highlights the therapeutic promise of botanical drugs and their metabolites, emphasizing critical findings regarding their inhibitory effects on PID-associated pathogens. Such insights provide valuable guidance for future therapeutic strategies and may support ongoing antibiotic discovery and development.